Individual Characteristics, Workload, Shift Work, and Work Fatigue among Stevedores at Ahmad Yani Port Ternate - Hairul Sinta; Herwin A. Hi. Adam; Ridwan Yamko (Poltekkes Kemenkes Palu, 2026)
Background: Work fatigue is an important occupational health and safety issue in port activities because stevedoring involves manual material handling, irregular schedules, and sustained physical effort. This study aimed to identify factors associated with work fatigue among local stevedores at Ahmad Yani Port, Ternate. Methods: This analytic observational study used a cross-sectional design. The population comprised all 110 local stevedores at Ahmad Yani Port, and all were included using total sampling. Work fatigue was measured using a structured questionnaire based on the Industrial Fatigue Research Committee (IFRC) instrument. The dependent variable was work fatigue; the independent variables were age, length of employment, nutritional status, physical workload, and work shift. Data were analyzed using IBM SPSS version 27. Univariate analysis described frequency distributions, and bivariate analysis used the chi-square test or Fisher’s exact test when assumptions were unmet, with a significance level of 0.05. Results: Most respondents were older (70.0%), had long employment duration (84.5%), had normal nutritional status (95.5%), had a light physical workload (57.3%), and experienced work fatigue (79.1%). Age (p = 0.004) and shift work (p = 0.004) were significantly associated with work fatigue, which was more frequent among older and night-shift workers. Length of employment (p = 0.972), nutritional status (p = 0.280), and physical workload (p = 0.529) were not significant. Conclusion: Age and shift work were the main factors associated with work fatigue. Prevention should prioritize age-sensitive job allocation, safer shift rotation, limiting consecutive night shifts, adequate rest, periodic health monitoring, and education.